Teachers’ Skill and Motivation in Using Information and Communication Technology - Paudel, Pitambar (Prithvi Journal of Research and Innovation, 2020)
Teaching and learning in the 21st century has been embedded with technology. Use of Information and Communication Technology (ICT) plays a crucial role in ameliorating knowledge acquisition in general and enhancing English Language mastering in particular. The government of Nepal has made provision of integrating ICTs in school education to enhance quality education and make both teachers and learners confident and competitive in the present global world. The teachers are the real implementers of the policy into practice. In this context, this research intended to investigate secondary level English teachers’ skill and motivation in using ICTs while teaching the English language. To achieve the objective, an explanatory sequential mixed research design was adopted. The survey questionnaire, unstructured interview and non-participant observation were used to determine the skills and motivation of forty secondary English teachers (20 from public and 20 from private schools). Two datasets, i.e. quantitative and qualitative were collected and analyzed sequentially. The findings of the research reveal that majority of the teachers have high motivation in using ICTs even though they are not skilful, knowledgeable and confident in handling and using new ICT tools and applications. The findings imply that teachers should be given opportunities for training on ICT use for building up their skill, motivation, knowledge and confidence.